ChemInform Abstract: Synthesis and Stability of Two‐Dimensional Ge/Sn Graphane Alloys. Issue 10 (March 2015) - Arguilla, Maxx Q.; Jiang, Shishi; Chitara, Basant; Goldberger, Joshua E.
Abstract Alloyed Ge/Sn graphane analogues are prepared by topochemical deintercalation of CaGe2‐2xSn2x (x = 0—0.09) in conc.